Alcune considerazioni sul pantheon slavo nell’opera di Aleksandr Radiščev Nekotorye soodraženija o slavjanskom panteone v tvorčestve Aleksandra Radiščeva - Garzonio, Stefano (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article is dedicated to the barely researched “Songs Sung in Competitions and Dedicated to Ancient Slavic Deities” by Aleksandr Radiščev. It is centered on a reconstruction of the old Slavic pantheon as suggested by the great Russian writer, on the literary and ideological presumptions of this reconstruction, and on a complex syncretic relationship between Radiščev’s “mythology” and other mythological systems.